ZNF804A variants relation to schizophrenia: a systematic review - Alsheikh, Ahmed M. (International Journal Of Community Medicine And Public Health, 2022)
Schizophrenia is a devastating mental disease; its etiology isn’t clearly understood. However, several hypotheses have been suggested; one of them is the involvement of the genetic factor. Rare and common variants of deoxyribonucleic acid (DNA) genes may contribute to the development of schizophrenia. ZNF804A is a gene encoding for zinc-finger protein, which has been reported to be associated with schizophrenia. However, a few recent studies were conducted on such subject, and there was no systematic analysis for such association. This study assessed the relation between ZNF804A variants and schizophrenia by reviewing the previous studies concerned with such subject. This systematic review was according to the preferred reporting items for systematic reviews and meta-analyses (PRISMA) checklist guidance for systematic review includes Pubmed, Embase, and Medline databases were used for searching for published articles between 2015 and 2021. The inclusion criteria were original articles conducted on schizophrenia patients, English, and full text- articles. As well as study the association between SCZ and ZNF804A variants. A total of 408 articles were obtained, only six articles were eligible for the inclusion criteria. The included studies involved a total number of 4,579 of them there were 2,738 schizophrenia patients and was conducted on four populations. All studies reported rs1344706 of the ZNF804A gene. The association between rs1344706 of the ZNF804A gene and SCZ was found in four studies out of the six studies, whereas the other two studies didn’t find such association. The association was concluded by the significant increase in the frequency of genotype and allele (A) among SCZ patients. ZNF804A gene variant at the rs1344706 was associated with the etiology of schizophrenia, with the A allele being the risk allele for the disease development.